Effect of Price, Quality Service and Trust to Customer Satisfaction - Margaret Guita; Erin Lianto; Kimberton Loni; Ricky Rafii Ritonga; Edisah Putra Nainggolan (International Journal Of Economics Social And Technology, 2023)
This researcher took object PT. Stara Bumi Surya because satisfaction decreased customers. Satisfaction customer is motivation customers to evaluate something product or service after use it. Price, quality service and trust be one reason descent satisfaction customers. Approach quantitative used as a method research. This research is manifold descriptive quantitative. Fits the purpose research, this research is descriptive and explanative. Population totaling 137 customers business and the sample for this study consisted of 102 individuals obtainedfrom formula Slovin. Up to 30 customers in the same company used to test validity and reliability. Analysis results linear regression shows satisfaction customers = 4. 609 + 0. 187 price + 0. 539 quality service + 0. 153 trust. kindly partial and simultaneous obtained results showthat price, quality service and trust in a manner Partial influential significant to satisfaction PT. Stara Bumi Surya. The adjusted R-squared value of 0. 551 means that variable free own influence to variable bound of 55. 1%, the remaining 44. 9% is influence variable free other